Tradisi dan Syariah: Penjemputan Kepala Desa Sebelum Sholat Idul Fitri di Desa Wainin Kecamatan Sanana Utara - Ichsan Fachri Kemhay; Rifani Gorontalo (Sekolah Tinggi Agama Islam Babussalam Sula, 2024)
In a religious context, traditions are often closely related to certain rituals, ceremonies or celebrations that have deep religious meaning. In major religions such as Islam, Christianity or Hinduism, traditions are not just cultural activities, but are also an integral part of worship and practice of the religion's teachings. The aim of this research is to analyze the tradition of picking up the village head before the Eid al-Fitr prayers in Wainin Village, North Sanana District. The method used in this research is qualitative research, using an approach, data collection techniques (interviews, observations, data documentation related to the tradition of picking up village heads before the Eid al-Fitr prayers in Wainin Village, North Sanana District. The research results show that this tradition is in line with sharia principles, maintaining social and cultural values ​​without violating religious teachings. The tradition of picking up the village head is carried out before Eid al-Fitr prayers and is a means of strengthening friendly relations between residents and also respecting the leaders in the village. Keywords: Tradition, Sharia, Pick-up, Village Head